Viewpoints on Media Effects: Pseudo-reality and Its Influence on Media Consumers - Madere, Carol M. (Lexington Books, 2017)
Viewpoints on Media Effects: Pseudo-reality and Its Influence on Media Consumers continues the ongoing research of media effects by illuminating not only the negative effects of media consumption, but also some of the pro-social aspects, with a special focus on social media. Recommended for scholars and researchers with an interest in media studies, specifically the exploration of media effects in various media. Also relevant scholars and researchers within the fields of communication studies, English, education, and sociology.